Achievements in Congenital Heart Defect Surgery. Issue 4 (27th January 2015) - Erikssen, Gunnar; Liestøl, Knut; Seem, Egil; Birkeland, Sigurd; Saatvedt, Kjell Johan; Hoel, Tom Nilsen; Døhlen, Gaute; Skulstad, Helge; Svennevig, Jan Ludvig; Thaulow, Erik; Lindberg, Harald Lauritz
<x xml:space="preserve">Abstract</x> Background— This article presents an update of the results achieved by modern surgery in congenital heart defects (CHDs) over the past 40 years regarding survival and the need for reoperations, especially focusing on the results from the past 2 decades. Methods and Results— From 1971 to 2011, all 7038 patients <16 years of age undergoing surgical treatment for CHD at Rikshospitalet (Oslo, Norway) were enrolled prospectively. CHD diagnosis, date, and type of all operations were recorded, as was all-cause mortality until December 31, 2012. CHDs were classified as simple (3751/7038=53.2%), complex (2918/7038=41.5%), or miscellaneous (369/7037=5.2%). Parallel to a marked, sequential increase in operations for complex defects, median age at first operation decreased from 1.6 years in 1971 to 1979 to 0.19 years in 2000 to 2011. In total, 1033 died before January 1, 2013. Cumulative survival until 16 years of age in complex CHD operated on in 1971 to 1989 versus 1990 to 2011 was 62.4% versus 86.9% (P<0.0001). In the comparison of patients operated on in 2000 to 2004 versus 2005 to 2011, 1-year survival was 90.7% versus 96.5% (P=0.003), and 5-year cumulative survival was 88.8% versus 95.0% (P=0.0003). In simple versus complex defects, 434 (11.6%) versus 985 (33.8%) patients needed at least 1 reoperation before 16 years of age. In complex defects, 5-year cumulative freedom of reoperation among patients operated on in 1990 to 1999 versus 2000 to 2011 was 66% versus 73% (P=0.0001). Conclusions— Highly significant, sequential improvements in survival and reductions in reoperations after CHD surgery were seen. A future challenge is to find methods to reduce the need for reoperations and further reduce long-term mortality.